Edibles and Canadian consumers' willingness to consider recreational cannabis in food or beverage products: A second assessment. (April 2020) - Charlebois, Sylvain; Music, Janet; Sterling, Brian; Somogyi, Simon
Abstract: Background: Canada is one of the few countries in the world to have legalized Cannabis. Cannabis was legalized in October 2018, but not cannabis-infused food products, also known as edibles. These products will be legalized by October 2019. This study examines how consumers view the legalization of cannabis-infused food products, when cannabis became legal, but not yet edible. Scope and approach: The study measured the perceptions on legalization, stigma, health risks and food safety on edibles. Underscored by this study is the growing uncertainty among most demographics, which suggests perhaps that public regulators have not connected well with the public when it comes to the food safety of edibles. Key Findings and Conclusions: Results show that while Canadians are ambivalent about social and public stigma, many remain concerned about inherent risks involved when consuming edibles. Concerns towards children and pets are also quite acute. Long term cannabis users are concerned about price and are still purchasing from old suppliers, which suggests that newly developed public distribution channels have been shunned to a certain degree. This study points to the need of more future evaluations of food safety measures and risk perception related to cannabis-infused food products. Highlights: Consumers carry doubts regarding the safe use of edible cannabis. Consumers of cannabis maintain former channels of distribution, despite legal status. Consumers perceive edible cannabis a more discreet form of cannabis use than smoking.